Low Six4 and Six5 gene dosage improves dystrophic phenotype and prolongs life span of mdx mice. (25th May 2016) - Yajima, Hiroshi; Kawakami, Kiyoshi
Abstract : Muscle regeneration is an important process for skeletal muscle growth and recovery. Repair of muscle damage is exquisitely programmed by cellular mechanisms inherent in myogenic stem cells, also known as muscle satellite cells. We demonstrated previously the involvement of homeobox transcription factors, SIX1, SIX4 and SIX5, in the coordinated proliferation and differentiation of isolated satellite cells in vitro . However, their roles in adult muscle regeneration in vivo remain elusive. To investigate SIX4 and SIX5 functions during muscle regeneration, we introduced knockout alleles of Six4 and Six5 into an animal model of Duchenne Muscular Dystrophy (DMD), mdx ( Dmd mdx /Y ) mice, characterized by frequent degeneration‐regeneration cycles in muscles. A lower number of small myofibers, higher number of thick ones and lower serum creatine kinase and lactate dehydrogenase activities were noted in 50‐week‐old Six4 +/− 5 +/− Dmd mdx /Y mice than Dmd mdx /Y mice, indicating improvement of dystrophic phenotypes of Dmd mdx /Y mice. Higher proportions of cells positive for MYOD1 and MYOG (markers of regenerating myonuclei) and SIX1 (a marker of regenerating myoblasts and newly regenerated myofibers) in 12‐week‐old Six4 +/− 5 +/− Dmd mdx /Y mice suggested enhanced regeneration, compared with Dmd mdx /Y mice. Although grip strength was comparable in Six4 +/− 5 +/− Dmd mdx /Y and Dmd mdx /Y mice, treadmill exercise did not induce muscle weakness in Six4 +/− 5 +/− Dmd mdx /Y mice, suggesting higher regeneration capacity. In addition, Six4 +/− 5 +/− Dmd mdx /Y mice showed 33.8% extension of life span. The results indicated that low Six4 and Six5 gene dosage improved dystrophic phenotypes of Dmd mdx /Y mice by enhancing muscle regeneration, and suggested that SIX4 and SIX5 are potentially useful de novo targets in therapeutic applications against muscle disorders, including DMD. Abstract : We used the mdx mice to investigate the function of Six4 and Six5 in muscle regeneration and demonstrated that low dosage of these genes in mdx mice was associated with improved dystrophic phenotypes and prolonged life span, probably due to enhanced skeletal muscle regeneration. This finding suggests that Six4 and Six5 are involved in the regulation of regeneration capacity and that these two transcription factors are potentially useful de novo targets in therapeutic applications against muscle disorders, such as DMD.